METHODOLOGICAL PRINCIPLES FOR EVALUATING THE ECONOMIC EFFICIENCY OF DISPOSAL OF RARE METALS FROM TECHNOLOGICAL WASTE OS SPECIAL STEEL - Hrigoriev, Dmytro; Skachkov, Viktor; Karpenko, Anna (Scientific Journal "Metallurgy", 2023)
The article proposes one of the directions for evaluating economic efficiency, taking into account non-traditional criteria that have developed during the utilization of rare metals in the metallurgy of special steels. The importance of the rational use of raw and energy resources, the use of man-made waste, secondary raw materials and the disposal of valuable components from their processing is shown. To increase the degree of utilization, additives of alloyed cyclone dust, which settles during the dispersion of liquid metal, were used. Optimum parameters of metallization of scale in capsules in heating furnaces together with heat-treated metal allow increase the degree of use of heating furnaces. The obtained spongy material in the capsule is used as an alloyed charge in the production of powder high-speed steels without any significant changes to the current technology, which made it possible to significantly reduce the costs of expensive rare elements and ferroalloys based on them. The factors that have been developed and have a decisive influence on the economic efficiency of the disposal of refractory elements at relatively low temperatures (no more than 1200 °С) by the proposed method have been identified. Determined factors affecting the efficiency of extraction of rare metals: the concentration of refractory elements in the used waste, consumption coefficients, the degree of their end-to-end utilization, reduction of the carbon content of the entire complex of refractory and active metals when conducting the process in systems with excess recovery potential and other factors. The economic expediency of recycling rare metals from the slag of high-speed steels is confirmed by calculations made on the basis of statistical processing of accounting data of active industrial steel production.